PENINGKATAN KUALITAS USAHA KESEHATAN SEKOLAH (UKS) MELALUI PENYEGARAN KADER UKS DI SMP SATYA SAI - Ni Made Nopita Wati; Ni Kadek Yuni Lestari; Desak Made Ari Dwi Jayanti; Tri Rahyuning Lestari (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background: Improving the quality of life of Indonesian people can be done through educational efforts both at school and outside of school. The School Health Business (UKS) is a basic health business aimed at schools and is the duty of the public health center to achieve health and improve learning achievement of school children). One of the functions of the UKS is as a forum for providing early health education especially for school children. Method: Before the implementation of the activity, the number of students involved amounted to 40 people, while the selection of students based on grade 8 and grade 9 would be selected again after getting extension activities and transforming as a UKS cadre. Activity Methods Used (1) Lecture and Demonstration Methods to discuss General Knowledge about School Health Enterprises (UKS), the role and participation of students in UKS activities, Efforts to Encourage, (2) Learning Methods Used to Transfer Assistance or Skills from the Value System Owned resource person to students. As a guest speaker providing health examination exercises for special UKS cadre students consisting of general physical examination and vital signs (blood pressure, temperature, pulse and breathing). Results: The results of the data collection obtained for SMP did not have its own UKS room ,but it was still combined with the primary school room which was still in the same building. Schools do not have UKS cadres and have never done UKS program activities. The level of student knowledge related to UKS is also very low. Conclusion: the level of student knowledge after counseling was found as many as 36 (86%) people have good knowledge and 6 people (14%) have enough knowledge. This shows that the provision of counseling and training can increase student knowledge. Suggestions, for SatyaSai Junior High School and Denut 3 Public Health Center to make a policy about the importance of UKS and to continue the program to have UKS space and to form a UKS structure so that good student behavior is formed to increase PHBS in schools and to follow up